"Inventario de especies arbóreas y arbustivas". En el marco del proyecto: Generación de conocimientos que aporte a la conservación y mejora de los ecosistemas que sostienen el pago por servicios ambientales. - Alvear Espinosa, Evelyn Carolina (2016)
The following study was conducted in the Kutukú Biological Forest Station, located in Sevilla Don Bosco parish of the Morona County, Province of Morona Santiago, Ecuador. The mail goal of the study was to determine the floristic composition of the tree and shrub strata present in the area. In order to achieve this goal, a forest census method was applied as the site features a mountainous. A one hectare forest quadrant was installed consisting of a base trailand, perpendicular to it, eight orientation trails. Individuals with a diameter at the height of chest (DBH) equal to or greater to 10 cm. As a result of the study, 272 individuals within the tree layer were registered, belonging to 21 families, 37 genus and 48 species; the most representative family is Euphorbiaceae with 51 individuals. In the shrub layer, 284 individuals were recorded belonging to 20 species, 10 genus and 10 families; the most outstanding family is Rubiaceae with 106 individuals. The biodiversity indexes calculated were Simpson, Shannon –Wiener and Margalef, used to determine dominance and diversity of the species found in the forest. In addition to this work, ethnobotanical surveys were implemented within the nearby community in order to determine uses and properties of plants; as a result, 24 medicinal plants were identified, of which Lippia citriodora (lemon verbena), Tournefortia fuliginosa (“malicagua”) and Croton lechleri (“sangre de drago”) outstand.